The Chemerin-CMKLR1 Axis is Functionally important for Central Regulation of Energy Homeostasis - Yun, Haesung; Dumbell, Rebecca; Hanna, Katie; Bowen, Junior; McLean, Samantha L.; Kantamneni, Sriharsha; Pors, Klaus; Wu, Qing-Feng; Helfer, Gisela (Frontiers in Physiology, 2022)
Chemerin is an adipokine involved in inflammation, adipogenesis, angiogenesis and energy metabolism, and has been hypothesized as a link between obesity and type II diabetes. In humans affected by obesity, chemerin gene expression in peripheral tissues and circulating levels are elevated. In mice, plasma levels of chemerin are upregulated by high-fat feeding and gain and loss of function studies show an association of chemerin with body weight, food intake and glucose homeostasis. Therefore, chemerin is an important blood-borne mediator that, amongst its other functions, controls appetite and body weight. Almost all studies of chemerin to date have focused on its release from adipose tissue and its effects on peripheral tissues with the central effects largely overlooked. To demonstrate a central role of chemerin, we manipulated chemerin signaling in the hypothalamus, a brain region associated with appetite regulation, using pharmacological and genetic manipulation approaches. Firstly, the selective chemerin receptor CMKLR1 antagonist α-NETA was administered i.c.v. to rats to test for an acute physiological effect. Secondly, we designed a short-hairpin-RNA (shRNA) lentivirus construct targeting expression of CMKLR1. This shRNA construct, or a control construct was injected bilaterally into the arcuate nucleus of male Sprague Dawley rats on high-fat diet (45%). After surgery, rats were maintained on high-fat diet for 2 weeks and then switched to chow diet for a further 2 weeks. We found a significant weight loss acutely and inhibition of weight gain chronically. This difference became apparent after diet switch in arcuate nucleus-CMKLR1 knockdown rats. This was not accompanied by a difference in blood glucose levels. Interestingly, appetite-regulating neuropeptides remained unaltered, however, we found a significant reduction of the inflammatory marker TNF-α suggesting reduced expression of CMKLR1 protects from high-fat diet induced neuroinflammation. In white and brown adipose tissue, mRNA expression of chemerin, its receptors and markers of adipogenesis, lipogenesis and brown adipocyte activation remained unchanged confirming that the effects are driven by the brain. Our behavioral analyses suggest that knockdown of CMKLR1 had an impact on object recognition. Our data demonstrate that CMKLR1 is functionally important for the central effects of chemerin on body weight regulation and neuroinflammation.